AKUNTANSI SUMBER DAYA MANUSIA - Naukoko, Princilvanno Andreas (JURNAL RISET AKUNTANSI GOING CONCERN, 2014)
Nowadays, accounting has developed more widely than just a study that provides financial information of organization. One of the development that still debated is about to put human resources as an asset. The ideas for put human resources as an asset are known as Human Resources Accounting (HRA). This research is for give a definition, recognition, measurement, and the constraints of HRA by using research literatures method. The results of this research shows that, the main problem in using human resources as an asset is about, how the organization measure the human resources and reveal it in financial report. As a conclusion from this research is HRA still needs further research, especially about to determine which kind of organization that is suitable to apply HRA in financial report.